2019
DOI: 10.1055/s-0039-1688917
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Medial Patellofemoral Ligament Reconstruction Can Be an Effective Procedure in Patellofemoral Instability with Risk Factors

Abstract: Patellofemoral instability is a severe problem in young and active patients. This pathology is influenced by ligamentous, bony, and neuromuscular parameters. The reconstruction of the medial patellofemoral ligament (MPFL) evolved to a primary procedure, but combined procedures were more frequently performed in the past years. However, additional operative procedures are associated with increased morbidity and no absolute indication can be identified in the literature. This study is intended to clarify whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
39
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 33 publications
0
39
0
2
Order By: Relevance
“…12 Commonly cited clinical thresholds for bony procedures include a TT-TG distance of greater than 16 mm or a CD index of greater than 1.2; however, the original surgical "a la carte menu" that established these criteria predates the surgical option of MPFL reconstruction. 8 There are few outcome studies of MPFL reconstruction evaluating the influence of TT-TG distance and patella alta on isolated MPFL reconstruction; however, several recent retrospective cohort studies 4,10,15,18,24 have demonstrated little influence of TT-TG distance and moderate patella alta on the outcomes of MPFL reconstruction. These studies suggest that isolated MPFL reconstruction can be successful in cases with a higher CD index and TT-TG distance than previously thought.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Commonly cited clinical thresholds for bony procedures include a TT-TG distance of greater than 16 mm or a CD index of greater than 1.2; however, the original surgical "a la carte menu" that established these criteria predates the surgical option of MPFL reconstruction. 8 There are few outcome studies of MPFL reconstruction evaluating the influence of TT-TG distance and patella alta on isolated MPFL reconstruction; however, several recent retrospective cohort studies 4,10,15,18,24 have demonstrated little influence of TT-TG distance and moderate patella alta on the outcomes of MPFL reconstruction. These studies suggest that isolated MPFL reconstruction can be successful in cases with a higher CD index and TT-TG distance than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…8 Patients with patella alta as defined by a Caton-Deschamps (CD) index of greater than 1.2 may be candidates for tibial tubercle distalization, 8 those with severe trochlear dysplasia may be candidates for trochleoplasty, 2 and those with an elevated TT-TG distance may benefit from tibial tubercle medialization. 8 These indications remain controversial, and several recent studies 4,10,15,18,24 have demonstrated good outcomes of isolated MPFL reconstruction in patients with some anatomic risk factors.…”
mentioning
confidence: 99%
“…Recently, another study supported the view that the isolated MPFL-R could be effective in treating RPD with bony risk factors, including increased FAA. 1…”
mentioning
confidence: 99%
“…Over the past decade, medial patellofemoral ligament (MPFL) reconstruction (MPFL-R) has been considered the most effective treatment for recurrent patellar dislocation (RPD), with a low redislocation rate. 1,2,10,13,19 However, because of the structural complexities of this disorder, unfavorable clinical outcomes after MPFL-R have also been reported recently. 23 It has been reported that isolated MPFL-R does not considerably improve patellar tracking or restore patellofemoral kinematics.…”
mentioning
confidence: 99%